Lithium Storage Mechanism and Application of Micron‐Sized Lattice‐Reversible Binary Intermetallic Compounds as High‐Performance Flexible Lithium‐Ion Battery Anodes. Issue 2 (4th December 2021) - Fang, Zhenhan; Duan, Shaorong; Liu, Haitao; Hong, Zixin; Wu, Hengcai; Zhao, Fei; Li, Qunqing; Fan, Shoushan; Duan, Wenhui; Wang, Jiaping
Abstract: A strategy of lattice‐reversible binary intermetallic compounds of metallic elements is proposed for applications in flexible lithium‐ion battery (LIB) anode with high capacity and cycling stability. First, the use of metallic elements can ensure excellent electronic conductivity and high capacity of the active anode substance. Second, binary intermetallic compounds possess a larger initial lattice volume than metallic monomers, so that the problem of volume expansion can be alleviated. Finally, the design of binary intermetallic compounds with lattice reversibility further improves the cycle stability. In this work, the feasibility of this strategy is verified using an indium antimonide (InSb) system. The volumetric expansion and lithium storage mechanism of InSb are investigated by in situ Raman characterization and theoretical calculations. The active material utilization is significantly improved and the growth of In whiskers is inhibited in the micron‐sized ball‐milled and carbon coated InSb (bInSb@C) anode, which exhibits a reversible capacity of 733.8 mAh g −1 at 0.2 C, and provides a capacity of 411.5 mAh g −1 after 200 cycles at 3 C with an average Coulombic efficiency of 99.95%. This strategy is validated in pouch cells, illustrating the great potential of lattice‐reversible binary intermetallic compounds for use as commercial flexible LIB anodes. Abstract : Lattice‐reversible binary intermetallic compounds (e.g., indium antimonide (InSb)) are proposed as a promising anode material for high‐performance flexible lithium‐ion batteries. InSb possesses the advantages of high conductivity and capacity, low volumetric expansion, and lattice‐reversibility, and the inherent whisker growth issue can be inhibited by carbon‐coating. The micron‐sized bInSb@C@CNT electrodes demonstrate outstanding capacity, cycle stability, rate performance, and high flexibility.